Razmerje med dolzino skoka in kotom skakalca pri smuearskih skokih - Dzelalija, M; Rausavljevic, N.; Jost, B. (Kinesiologia Slovenica, 2003)
Using a simple physical model of ski jumping the current study investigates the relationship between a ski jumper`s position angle during the flight phase and the jump length as well as other physics variables. The physical parameters of the jump (velocity, current drag, jump length) were calculated taking into account height of the jumping hill, inclination of the outrun, and position of the system jumper-skis during the flight phase. The analysis of the jump curve was made on the basis of the angle between the flight trajectory of the common centre of gravity and the x-axis. For the analysis of the jumper`s position during the flight phase the angle between the upper part of the body and the flight trajectory of the common centre of gravity of the body was chosen. In the computer simulation of the jump length two variants of the course of the angle . were used. The flight velocity was very similar in both variants. Immediately after take-off, the resultant velocity v(t) and its horizontal component vx(t) slightly decreased. After that the resultant velocity increased constantly due to the constant increase in the vertical component vy(t). Due to the current drag the horizontal flight component vx(t) decreased constantly during the entire flight phase. The current drag FD(t) and lift components FL(t) rose to a greater extent in the changeable ski jumper`s position angle.